2012
DOI: 10.1021/ja302071t
|View full text |Cite
|
Sign up to set email alerts
|

Switching Kr/Xe Selectivity with Temperature in a Metal–Organic Framework

Abstract: Krypton (Kr) and xenon (Xe) adsorption on two partially fluorinated metal-organic frameworks (FMOFCu and FMOFZn) with different cavity size and topologies are reported. FMOFCu shows an inversion in sorption selectivity toward Kr at temperatures below 0 °C while FMOFZn does not. The 1D microtubes packed along the (101) direction connected through small bottleneck windows in FMOFCu appear to be the reason for this peculiar behavior. The FMOFCu shows an estimated Kr/Xe selectivity of 36 at 0.1 bar and 203 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 35 publications
(27 reference statements)
2
116
1
Order By: Relevance
“…MOFs have several advantages as compared to zeolites: cheaper and simpler synthesis, high diversity of pore structures, and numerous possibilities for postsynthetic modifications. Despite the importance of MOFs for noble gas storage and separation, only a few studies of krypton and xenon adsorption are reported to date [1][2][3][4][5][6][7][8][9][10][11][12] and only three studies of adsorption sites of noble gases in MOFs by means of X-ray or neutron diffraction, [13][14][15] despite the fact that the major adsorption sites and their binding energies are the key features of a material that determines its adsorption properties at a given temperature and pressure, and their identification is a basis for further modifications of the crystal structure of the MOF in order to achieve maximal storage capacity and selectivity. The study of noble gas adsorption in HKUST-1 15 revealed that the interaction of noble gases with MOFs can be completely different from the adsorption of other atoms and molecules like D 2 , C 2 H 2 , CO 2 , or CH 4 (methane is a nonpolar gas whose diameter and polarizability are similar to those of Kr).…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have several advantages as compared to zeolites: cheaper and simpler synthesis, high diversity of pore structures, and numerous possibilities for postsynthetic modifications. Despite the importance of MOFs for noble gas storage and separation, only a few studies of krypton and xenon adsorption are reported to date [1][2][3][4][5][6][7][8][9][10][11][12] and only three studies of adsorption sites of noble gases in MOFs by means of X-ray or neutron diffraction, [13][14][15] despite the fact that the major adsorption sites and their binding energies are the key features of a material that determines its adsorption properties at a given temperature and pressure, and their identification is a basis for further modifications of the crystal structure of the MOF in order to achieve maximal storage capacity and selectivity. The study of noble gas adsorption in HKUST-1 15 revealed that the interaction of noble gases with MOFs can be completely different from the adsorption of other atoms and molecules like D 2 , C 2 H 2 , CO 2 , or CH 4 (methane is a nonpolar gas whose diameter and polarizability are similar to those of Kr).…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Xenon and krypton are also products of the nuclear fission of uranium and plutonium; 40 porous materials could be used to capture the radioactive xenon and krypton in the processing of used nuclear fuel. [47][48][49] Experiments regarding xenon and krypton adsorption 44,48,[50][51][52][53][54][55][56][57][58][59][60][61][62] suggest that it may be feasible to use nanoporous materials in an adsorption-based process to separate a Xe/Kr mixture.…”
mentioning
confidence: 99%
“…22 This particular MOF was specifically selected by us for Xe/Kr adsorption studies because of its potential to exhibit a "molecular sieving" effect. The pore structure contains tubular cavities (ca.…”
Section: Fmofcumentioning
confidence: 99%